Implementing world class commissioning competencies - McCafferty, Sara; Williams, Lestyn; Hunter, David; Robinson, Suzanne; Donaldson, Cam; Bate, Angela (IngentaConnect Publication, 2012)
Background: The world class commissioning (WCC) programme was introduced in the English NHS in 2007 to develop primary care trust (PCT) commissioning of health services. There has been limited evaluation of health commissioning initiatives over the years and in particular little is known about how commissioners interpret and implement initiatives and guidance intended to strengthen commissioning. This research explores the development and implementation of WCC and draws implications for future commissioning arrangements.Methods: This research draws on interviews with key informants (n = 6) and a literature review to analyse the aims of, and stimulus for, WCC. In-depth interviews (n = 38) were conducted in three PCTs in the north of England in 2009 to analyse the interpretation and implementation of WCC.Results: The aims and rationale of WCC, in particular, the specification of commissioning skills and the aspirations to improve health outcomes, were largely welcomed and supported by interviewees. However, the implementation of WCC posed a number of challenges, including: availability of resources and knowledge; lack of a supportive organizational culture and networks; and the dominance of central government control.Conclusions: The findings have implications for emerging clinical commissioning groups (CCGs) in the English NHS. Specifically, the research highlights the need for a system-wide approach to improving commissioning, including appropriately aligned policy and objectives underpinned by a co-ordinated and supportive organizational culture.